A sexual murder prevented? A case study of evidence-based practice. Issue 5 (3rd September 2021) - Greenall, Paul V; Millington, James
ABSTRACT: Clinical work with offenders with histories of sexual violence is an important aspect of forensic practice. A key feature of this is the clinical interview, which allows individual and offence-related issues to be explored. Research suggests that some sexual offences contain sexual motivations and may therefore be related to deviant sexual fantasies. This case study reports on the assessment and formulation of a patient detained in a regional secure unit. Although he had no previous sexual convictions, he had a history of being sexually violent towards others. During clinical interviews the patient disclosed having deviant sexual fantasies for several years relating to the rape and strangulation of women. These fantasies fuelled his daily masturbatory behaviour and he reported several attempts to enact them before his detention in hospital. Once in hospital the object of his sexual desires became a female nurse, whom he wanted to rape and strangle, the idea of which again fuelled his daily masturbatory behaviour. These disclosures necessitated preventative measures being taken by his clinical team and re-enforced the importance of giving due consideration to violent sexual fantasies and the importance of evidence-based risk formulations that inform the care and management of forensic patients.